Hydrogel-incorporated Colorimetric Sensors with High Humidity Tolerance for Environmental Gases Sensing - Yu, Jingjing (Sens Actuators B Chem, 2021)
Humidity interferes most gas sensors, especially colorimetric sensors. The conventional approaches to minimize the humidity interference in colorimetric gas sensing require using extra components, causing unwanted analytes loss, or limiting the choices of sensing probes to only hydrophobic ones. To explore the possibility of minimizing the humidity interference in a hydrophilic colorimetric sensing system, we have developed a hydrogel-incorporated approach to buffer the humidity influence on the colorimetric gas sensing. The hydrogel-incorporated colorimetric sensors show not only high humidity tolerance but also the improved analytical performance. The accuracy and reliability of the hydrogel-incorporated colorimetric sensors have also been validated in field tests. This hydrogel-incorporated approach will open up an avenue to implement hydrophilic recipes into colorimetric gas sensors and extend the application of colorimetric sensors to humid gases detection.